2023
DOI: 10.1121/10.0023960
|View full text |Cite
|
Sign up to set email alerts
|

Receptive vocabulary predicts multilinguals' recognition skills in adverse listening conditions

Lexia Suite,
Galia Freiwirth,
Molly Babel

Abstract: Adverse listening conditions are known to affect bilingual listeners' intelligibility scores more than those of monolingual listeners. To advance theoretical understanding of the mechanisms underpinning bilinguals' challenges in adverse listening conditions, vocabulary size and language entropy are compared as predictors in a sentence transcription task with a heterogeneous multilingual population representative of a speech community. Adverse listening was induced through noise type, bandwidth manipulations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Given these facts paired with our definition of late bilingual as learning English after age 12, it is safe to assume that among the late bilinguals in our study, older SMs had been speaking English for longer than younger SMs at the time of testing. More experience using English would give older late bilinguals an advantage over their younger peers, perhaps through increased English receptive vocabulary size, which has recently been shown to predict the transcription accuracy of English words presented in noise in a diverse group of bilinguals (Suite et al, 2023). SNR also interacted with age and with listener group.…”
Section: Differences Between Monolinguals and Bilingualsmentioning
confidence: 95%
See 3 more Smart Citations
“…Given these facts paired with our definition of late bilingual as learning English after age 12, it is safe to assume that among the late bilinguals in our study, older SMs had been speaking English for longer than younger SMs at the time of testing. More experience using English would give older late bilinguals an advantage over their younger peers, perhaps through increased English receptive vocabulary size, which has recently been shown to predict the transcription accuracy of English words presented in noise in a diverse group of bilinguals (Suite et al, 2023). SNR also interacted with age and with listener group.…”
Section: Differences Between Monolinguals and Bilingualsmentioning
confidence: 95%
“…In two studies involving Italian-English bilingual adults, English SiN perception was found to be less accurate for bilinguals who used relatively more Italian (and therefore relatively less English) at the time of testing (MacKay et al, 2001;Meador et al, 2000). In another study involving a community sample of bilingual adults, speech recognition accuracy in a variety of degraded conditions decreased with increasing language entropy (Suite et al, 2023), which is a metric derived from self-reported language use that quantifies the proportion of time a bilingual uses different languages in a given context (Gullifer & Titone, 2020). In other studies, the relationship between language use and SiN recognition was not significant after the influence of other factors such as English AoA and proficiency were accounted for (Oyama, 1978;Shi, 2012;Shi & Sánchez, 2010).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations